Investigation of online counseling with solution focused brief counseling-based implementation for students with severe academic stress conditions - Zadrian Ardi; Ifdil Ifdil; Chibueze Tobias Orji; Nilma Zola (Jurnal Konseling dan Pendidikan, 2022)
Students are susceptible to feeling pressure as a manifestation of the changes experienced during their educational process. These changes present themselves in a variety of different ways. This state is reasonably frequent among students, mainly when supporting causes of pressure are present. Some examples of these circumstances include living away from parents, shifting patterns of academic interactions from high school, differing academic expectations, and socio-cultural shifts. Moving beyond the theoretical foundation, empirical investigations, and phenomena in the area, there is a need for in-depth research and studies about attempts to identify models that alleviate the academic stress experienced by students. The Solution Focused Brief Counseling (SFBC) technique combined with the internet, and online media is one of these approaches. The goal of this research was to determine whether or not the SFBC method combined with the model of distant counseling might successfully alleviate the academic stress experienced by first-year students. The number of participants in this research was cut down to five college students to meet the research requirements. The design and analysis of the research adhere to the premise of using a single-subject experimental design combined with visual analysis. The findings demonstrated an overall reduction in the amount of academic stress experienced by students after two sessions, as well as an improvement in their condition by the time the session was through